Caring During COVID-19: Reconfigurations of Gender and Family Relations During the Pandemic in Switzerland - Bühler, Nolwenn; Pralong, Mélody; Rawlinson, Cloé; Gonseth, Semira; D’Acremont, Valérie; Bochud, Murielle; Bodenmann, Patrick (Frontiers in Sociology, 2021)
COVID-19 caused major changes in private and public arenas. Individuals were forced to reorganise their daily lives in response to the restrictive measures imposed by governments. The redistribution of gender roles and the responsibility for care provides an example of the reconfigurations that took place during the pandemic. This article sheds light on the implications of the pandemic for gender inequalities by exploring how care work was reconfigured as women and men sought to protect family members and navigated risks of infection. The study is based on qualitative data – interviews and observations – gathered in an interdisciplinary medical anthropology project. In the article, the authors focus on seven cases selected from a larger corpus to illustrate how reconfigurations of the gendered division of care work within families shifted during the pandemic as men assumed greater moral responsibility for safeguarding family members, without infringing the norms of masculinity. The first part of the article explores the intensification of care activities during lockdown for women living in the Canton de Vaud in Switzerland. The second part centres on the moral responsibility and duty for women and men to protect family members from viral exposure. The results from the study confirm not only that most care activities continued to be delegated to female family members, but also that men’s roles evolved. While their safeguarding role can be understood as a new form of caring for men, the findings suggest that it was essentially crisis specific and did not challenge masculinity norms. The extent to which this reconfiguration of gender roles might have a longer-term impact on gender inequalities remains to be seen. Meanwhile, these observations could have important implications for policies aimed at mitigating the medium and long-term effects of the pandemic on gender inequality.